The Public Space of âJogja Fashion Week Carnivalâ and Cosplay Clothing in Yogyakarta - Setiawan, Deni; Haryono, Timbul; Burhan, Agus (Universitas Negeri Semarang, 2014)
The concept of an ideal public space does not just focus on the interests of a particular group or community, but rather focus on the space of social activities that represent each audience or spectator in that society. Arts and cultural activities are part of it; although the concept of public space is still abstract to represent every social individual. However, the presence of public space has created a mediation space for all forms of communication. Mediation space is considered as a crucial feature, not only as a promotional sphere but also as a place to exchange and communicate all forms of ideology, art, and culture. Art activities such as Jogja Fashion Week Carnival and Cosplay clothing performance in public spaces provide opportunities for communities or individuals, to make this activity as a public performance and part of public art. Public art tends to be creative, free, and sometimes not accompanied by a theoretical perspective, as other arts are. Art activities in public spaces which are part of the social and cultural activities are essentially standing on the ideology that have been set up for a particular interest. The interest is disseminated using mass media and advertisment. Audience or public art connoisseur in public spaces should be more intelligent and critical to accept all kinds of art activities and performances. Therefore the performance will have a balanced communication.AbstrakKonsep ruang publik yang ideal tidak saja berbicara kepentingan golongan atau komunitas tertentu, tetapi lebih fokus pada wadah aktivitas sosial yang mewakili setiap pendatang atau penonton. Termasuk didalamnya adalah aktivitas seni dan budaya, walaupun konsep ruang publik masih dapat dikatakan abstrak untuk mewakili setiap individu sosial. Akan tetapi dengan adanya ruang publik telah menciptakan ruang mediasi bagi segala macam bentuk komunikasi. Ruang mediasi ini dipandang penting, tidak saja dijadikan ranah promosi, lebih mendalam adalah untuk bertukar dan tempat komunikasi segala macam bentuk ideologi, kesenian, dan kebudayaan. Aktivitas seni semacam Jogja Fashion Week Carnival dan pagelaran pakaian cosplay pada ruang publik memberikan kesempatan bagi komunitas atau individu, untuk menjadikan aktivitas ini sebagai tontonan dan bagian seni publik. Seni publik ini tentu saja lebih cenderung lebih kreatif, bebas, dan terkadang tidak diiringi dengan perspektif teoretis, seperti yang dilakukan seni lainnya. Aktivitas seni pada ruang publik, merupakan bagian dari aktivitas sosial dan budaya, hakikatnya berdiri pada ideologi yang telah diatur untuk satu kepentingan, yang disebarluaskan menggunakan media massa dan iklan. Penonton atau masyarakat penikmat seni pada ruang publik, harus lebih cerdas dan kritis untuk menerima segala macam bentuk sajian aktivitas seni, sehingga sajian tersebut memiliki komunikasi yang seimbang.